Hamadab, Sudan: Die Arbeiten der Jahre 2013 und 2014 - Wolf, Pawel; Nowotnick, Ulrike (e-Forschungsberichte des DAI, 2023)
The urban town of Hamadab flourished during the Meroitic period (3rd century BC to 4th century AD) 3 km south of the ancient capital Meroe on the east bank of the Nile. It is subject of a German-Sudanese research project since 2001. The report summarises our recent fieldwork at Hamadab in 2013 and 2014, which focused on excavations in the settlement’s Upper Town and on a new study of the historic land use in relation to the environment of the Meroe-Hamadab region.